2011
DOI: 10.1155/2011/718710
|View full text |Cite|
|
Sign up to set email alerts
|

Safety and Clinical Usage of Newcastle Disease Virus in Cancer Therapy

Abstract: Newcastle disease virus (NDV) is an avian virus that causes deadly infection to over 250 species of birds, including domestic and wild-type, thus resulting in substantial losses to the poultry industry worldwide. Many reports have demonstrated the oncolytic effect of NDV towards human tumor cells. The interesting aspect of NDV is its ability to selectively replicate in cancer cells. Some of the studies have undergone human clinical trials, and favorable results were obtained. Therefore, NDV strains can be the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
76
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(80 citation statements)
references
References 83 publications
(181 reference statements)
2
76
0
2
Order By: Relevance
“…NDV is inherently tumor selective and oncolytic. The tumor selective property of NDV, coupled with compelling preclinical and phase I/II studies in human subjects, has identified NDV as an attractive virotherapy candidate (9,24,27).…”
mentioning
confidence: 99%
“…NDV is inherently tumor selective and oncolytic. The tumor selective property of NDV, coupled with compelling preclinical and phase I/II studies in human subjects, has identified NDV as an attractive virotherapy candidate (9,24,27).…”
mentioning
confidence: 99%
“…54 Depending on the mode of oncolysis, NDVs have been evaluated and classified as lytic or non lytic strains. The lytic strains cause syncytia formation to induce changes in the plasma membrane resulting in lysis of target cells.…”
Section: Mode Of Actionmentioning
confidence: 99%
“…Over the past century, a number of oncolytic viruses have been discovered, such as mumps, measles, adenovirus, reovirus, Newcastle disease virus (NDV), and others. 3,4 Newcastle disease virus as a vector for gene therapy is under clinical evaluation. 5 Newcastle disease virus is a member of the Avulavirus genus in the Paramyxoviridae family.…”
Section: Introductionmentioning
confidence: 99%
“…The inherent viral oncolytic properties are believed to be derived from defective IFN signaling pathways in tumor cells. 3,5,8 The development of reverse genetics technology for NDV enable us to modify the NDV genome as well as introduce foreign sequences to refine the antitumor activity. [9][10][11][12][13] Previous studies in our laboratory showed that recombinant NDVs (rNDVs) expressing Trail, interleukin (IL) 15, and IL-2 are promising antitumor agents.…”
Section: Introductionmentioning
confidence: 99%